COMPARATIVE DYNAMIC ANALYSIS OF RCC AND COMPOSITE HIGH-RISE BUILDINGS FOR LATERAL FORCES - G S, Sandeep; Kumar, M Prasanna; V Navale, Sawan; Sathyanarayan, Srinivas (Journal of Applied Engineering Science, 2025)
This study presents a comprehensive comparative analysis of reinforced cement concrete (RCC) and various composite buildings subjected to wind and seismic forces. RCC members, while prone to buckling, experience creep and shrinkage over time, which can affect long-term stability and performance. Conversely, steel members, composed of slender plate elements, are susceptible to local and lateral buckling, which can compromise structural integrity during wind and seismic events. Composite buildings effectively combine strengths of both materials, utilizing the robustness of RCC and the flexibility of steel to optimize performance and resilience. In the present study, (G+25) storey high-rise regular building and (G+25) storey high-rise building with vertical geometric irregularity considering RCC and composite concrete elements (columns, beams and slabs) are modelled using ETABS 2021 and analysed for lateral forces. Response spectrum analysis is adopted to provide insights into dynamic response of buildings under wind and seismic loads. The study aims to evaluate structural behaviour of RCC, and composite buildings located in Greater Noida, India for lateral forces. Key dynamic response parameters such as storey drift, storey stiffness, storey displacement and base shear of RCC and composite buildings are compared. Building model with concrete encased I-section composite column, RCC beam and RCC slab observed to exhibit better performance over conventional RCC buildings with higher story stiffness, lesser storey displacements and story drifts for both regular and geometrical vertical irregular buildings. The study finds its application in high-rise regular and vertical geometric irregular buildings taking the advantage of reduced overall weight and improved response to lateral forces.
Keywords: composite structural elements, reinforced cement concrete, ETABS 2021, response spectrum analysis, vertical geometric irregularity